Purification, characterization and comparison of Penicillium purpurogenum β‐glucuronidases expressed in Escherichia coli and Pichia pastoris. Issue 10 (29th April 2013) - Zou, Shuping; Guo, Shuyuan; Kaleem, Imdad; Li, Chun
Abstract Background To investigate the effects of post‐translational modifications in different recombinant expression systems on the catalytic properties of recombinant β‐glucuronidase. The β‐glucuronidase (GUS) gene from Penicillium purpurogenum Li‐3 was cloned and successfully expressed in Escherichia coli BL21 and Pichia pastoris G115. Results The recombinant E. coli produced a 15‐fold increased level of β‐glucuronidase while the recombinant P. pastoris strain produced a 6.9‐fold increased level of β‐glucuronidase compared with their parent strains. The β‐glucuronidases from recombinant E. coli (PGUS‐E) and P. pastors (PGUS‐P) were purified to 35.9‐ and 47.4‐fold, respectively, through affinity, ion exchange and gel filtration chromatography. PGUS‐E from E. coli was a non‐glycosylated protein with an apparent molecular mass of 72.43 kDa, while PGUS‐P from P. pastors was appropriately glycosylated with a molecular mass of 78.83 kDa measured by MALDI/TOF‐MS. Although both recombinant β‐glucuronidases exhibited similar pH optima, the glycosylated PGUS‐P showed a significantly higher thermal stability and less sensitivity to metal ions compared with the non‐glycosylated PGUS‐E. The glycosylated PGUS‐P also displayed lower Km values, and higher kcat/Km ratios than the non‐glycosylated enzyme towards glycyrrhizin. Conclusion These results revealed the key role of post‐translational modifications in the P. pastors expression system on the catalytic properties of β‐glucuronidase and its potential stability over the prokaryotic expression system which could be applied as an important tool for the functional enhancement of industrial enzymes. © 2013 Society of Chemical Industry